Prognozowanie cen energii elektrycznej z wykorzystaniem SSN na Towarowej Giełdzie Energii SA - Halicka, Katarzyna (Forecast of Energy Prices on Polish Power Exchange with Use of Neural Network, 2005)
In this paper the use of neural network to forecast prices of energy on Polish Power Exchange is presented. Three prognostic models, with different input variables and number of neurons in layers, were build. The following variables were used in the neural network as input: demand for energy, air temperature, wind speed, cloud conditions and rainfall. On the basis of constructed models the prediction of energy prices was done and then evaluation of forecasts quality was performed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 228-237